2019
DOI: 10.17503/agrivita.v41i2.2105
|View full text |Cite
|
Sign up to set email alerts
|

Conidial Density and Viability of Beauveria bassiana Isolates from Java and Sumatra and Their Virulence Against Nilaparvata lugens at Different Temperatures

Abstract: The brown planthopper (BPH), Nilaparvata lugens can cause direct damage and transmit rice diseases. Beauveria bassiana is used to control BPH, however the success of the fungal efficacy on rice fields is affected by external factors, such as temperature. This research aimed to evaluate the conidial viability and density of B. bassiana isolates from Java and Sumatra, exposed to 25 and 34°C and their virulence against BPH nymphs. Twenty six isolates of B. bassiana cultures incubated at 25 and 34°C for 7 days wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
(21 reference statements)
1
24
2
Order By: Relevance
“…The larvae that were sick from eating the leaves applied to culture filtrates showed a difference when compared to the larvae that died from being infected with B. bassiana spores. According to Safitri et al (2018) and Sumikarsih et al (2019), the larvae that died as a result of being infected with the entomopathogenic fungus spores showed symptoms such as the body decreasing in size, shrinking, drying, and having no smell; however, from the host insect's body grew the fungus in the form of mycelia, hyphae and spores on the surface of the integument. The non-growth of B. bassiana in larvae of this study resulted from the loss of mycelia, hyphae, and spores in the culture filtrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larvae that were sick from eating the leaves applied to culture filtrates showed a difference when compared to the larvae that died from being infected with B. bassiana spores. According to Safitri et al (2018) and Sumikarsih et al (2019), the larvae that died as a result of being infected with the entomopathogenic fungus spores showed symptoms such as the body decreasing in size, shrinking, drying, and having no smell; however, from the host insect's body grew the fungus in the form of mycelia, hyphae and spores on the surface of the integument. The non-growth of B. bassiana in larvae of this study resulted from the loss of mycelia, hyphae, and spores in the culture filtrate.…”
Section: Discussionmentioning
confidence: 99%
“…Entomopathogenic fungi are those of soil parasitizing and killing insects pest and proved superior in biological control. However, Beauveria bassiana and Metarhizium anisopliae are two examples of entomopathogenic fungi (Herlinda et al 2018a), whose utilization is often constrained by external factors (Sumikarsih et al 2019). B. bassiana is facultative parasites that can be parasitic on insects and saprophytes in soil or organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…The entomopathogenic fungi already isolated from T. molitor larvae were identified based on the morphological characteristics, for example, the colony colors and shapes of culture on SDA, conidia shape and color using a taxonomic book of Humber (2005) and El-Ghany (2015). The conidia density was calculated using the method of Sumikarsih et al (2019), while the viability was observed by growing 10 μL of fungal conidia suspension (1 x 10 6 conidia mL -1 ) on 2% of agar-water medium, containing 2 g of agar which was given 100 mL distilled water (w/v), then the culture was incubated for 2 x 24 hours.…”
Section: Isolation and Identification Of The Entomopathogenic Fungimentioning
confidence: 99%
“…The soil which is a fungal habitat during the saprophytic phase has high entomopathogenic fungi inoculum potential, especially those close to plant roots (Safitri et al 2018) and is effective in killing the insect pests (Ayudya et al 2019;Sumikarsih et al 2019;Gustianingtyas et al 2020). Research results from other countries show the high pathogenicity of entomopathogenic fungi from soil in controlling S. frugiperda population.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that entomopathogenic fungi can kill rice insect pests. For example, Beauveria bassiana effectively kills brown planthopper (Sumikarsih et al 2019). Filtrate B. bassiana culture is very toxic to Spodoptera litura larvae (Ayudya et al 2019).…”
Section: Introductionmentioning
confidence: 99%